Presentasi Diri Pelatih Marching Band (Studi Dramaturgi pada Marching Band Universitas Sebelas Maret Surakarta) - Muhammad Fauzi; Yosafat Hermawan Trinugraha; Yuhastina Yuhastina (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
Marching Band is the art of playing musical instruments combined with structured formation movements so that it becomes a complete performance. Being a Marching Band trainer, especially in the Marching Band UNS (MB UNS), is the same as being a teacher. The coach will form a new personality for himself when he wants to train his players. The purpose of this study was to find out the factors that cause the MB UNS trainers to form their self-presentation while in the field as well as the concepts of the front stage and back stage of the MB UNS trainers in forming their self-presentation during practice. This study used a qualitative method with a case study research design applying the dramaturgical theory perspective of Erving Goffman. Data collection techniques used are interviews, observation, and documentation. The results showed that the factors that led to the formation of the self-presentation of MB UNS coaches were experience, personal reasons, and professional demands. The front stage form of the MB UNS trainers tended to be firm and disciplined, while their back stage form became more friendly.